Electromyographic analysis of the support scale in gymnastics and its related preconditioning strengthening exercises - Rosaci, G.; Nigro, F.; Cortesi, M.; Ciacci, S.; Bartolomei, S.; Fantozzi, S. (The Journal of Strength and Conditioning Research, 2025)
The support scale (SS) is a common upper body skill in gymnastics. Athletes typically introduce preconditioning strengthening exercises (PSEs) in their training routines to prepare this strength element. Despite the popularity of these exercises, their effectiveness in reproducing the muscle involvements of the SS is unknown. The aim of this study is to compare the muscular excitations, coactivation indices, and synergies between the SS and its related PSEs. Seven high-level ring specialist gymnasts (age: 23.9 ± 4.0 years, height: 165.9 ± 2.8 cm, body mass: 65.6 ± 3.1 kg, experience: 13.0 ± 3.0 years) performed the SS and 5 PSEs. Electromyographic activities of the pectoralis major (clavicular part), latissimus dorsi, triceps (long head), infraspinatus, trapezium (transverse), serratus anterior, biceps brachii, and anterior deltoid were recorded, and muscle synergies were studied. Large differences between the SS and its 5 PSEs were detected in the muscle activity of trapezius (F = 8.937; p < 0.001; n2 = 0.641), pectoral (F = 5.235; p = 0.002; n2 = 0.512), and biceps muscles (F = 10.359; p < 0.001; n2 = 0.674). The coactivation was different in the biceps/triceps ratio (F = 5.980; p < 0.001; n2 = 0.545) and the serratus/trapezium ratio (F = 8.043; p < 0.001; n2 = 0.617). The analysis of muscle synergies showed different simultaneous muscular activation in the PSEs compared with the SS. Thus, the results of this study provide evidence for a different use of PSEs in the training routine to improve SS performance.